Pelatihan Administrasi dan Pemasaran Produk Olahan Pangan Lokal di Kabupaten Tangerang - Oktarina, Thina; Sudiyono, Rachma Nadhila; winanti, winanti; Yulia, Yayah; Maesaroh, Siti; Lestari, Sri; Rahmawati, Yunita; Haniyah, Haniyah; Asnaini, Sri Wahyuni; Purwaningrum, Dwi; Nurasiah, Nurasiah; Arizqa, Winanda Muftia; Fajriah, Rosika Nur (IAHN Gde Pudja Mataram, 2025)
There are still many UMKM actors engaged in processed food who understand about good and correct administration and marketing so that many of them close and go bankrupt due to not understanding both of these things. The purpose of this training activity is to provide understanding to UMKM actors of processed products regarding proper business administration and marketing. Participants consist of UMKM actors in Tangerang Regency. The activity lasted for one day and went smoothly. All participants were enthusiastic about following this activity until it was finished. It is hoped that with this training activity, UMKM actors of processed products who attend can understand proper business administration and marketing so that income increases and business sustainability can be achieved